-16=y-13

Simple and best practice solution for -16=y-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=y-13 equation:


Simplifying
-16 = y + -13

Reorder the terms:
-16 = -13 + y

Solving
-16 = -13 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-16 + -1y = -13 + y + -1y

Combine like terms: y + -1y = 0
-16 + -1y = -13 + 0
-16 + -1y = -13

Add '16' to each side of the equation.
-16 + 16 + -1y = -13 + 16

Combine like terms: -16 + 16 = 0
0 + -1y = -13 + 16
-1y = -13 + 16

Combine like terms: -13 + 16 = 3
-1y = 3

Divide each side by '-1'.
y = -3

Simplifying
y = -3

See similar equations:

| 60-.04x=80 | | 3/10-(-2/3) | | -3=z-18 | | 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x | | (x-3+5i)(x-3-5i)=0 | | 420=(2x+5)x | | 3(5-2m)=27 | | 798x+2(60)=500x |

Equations solver categories